Algorithm Design of Digital Watermarking Scheme for Multi-frames Medical Images - Khor, Hui Liang; Liew, Siau-Chuin; Jasni, Mohamad Zain (IEEE, 2015)
With the advancement of technology in communication network, it facilitated digital medical images transmitted to healthcare professional via internal network (e.g. PACs) or public network (e.g. Internet), in which pose a threat to digital medical images security, such as image tampering, and results a clinical misdiagnosis and treatment.Thus a reversible watermarking is introduced to maintain the integrity of medical images. There have been a number of researches done on watermarking scheme on single frame medical image, in which it is impractical in real world environment, where modalities are consist of multi-frames.This paper presented a conceptual design on developing a reversible watermarking scheme (tamper localization and recovery watermarking scheme) on medical images in multiframes environment. The watermarking process was applied on each frame in sequence. Time consuming has become a limitation of sequential watermarking process on multiframes medical images, especially in a large dataset of medical images. In order to solve the sequential problem concern, a parallel computing is recommended. Parallel watermarking could be achieved by utilised multicore technologies.